1992
DOI: 10.1128/jb.174.1.24-29.1992
|View full text |Cite
|
Sign up to set email alerts
|

The CobII and CobIII regions of the cobalamin (vitamin B12) biosynthetic operon of Salmonella typhimurium

Abstract: A detailed deletion map of the CobIH and CobIII regions of the cobalamin biosynthetic (cob) operon of SalmoneUa typhimurium LT2 has been constructed. The CobII region encodes functions needed for the synthesis of lower ligand 5,6-dimethylbenzimidazole (DMB); CobUI encodes functions needed for the synthesis of the nucleotide loop that joins DMB to the corrin macrocycle. The genetic analysis of 117 deletion, insertion, and point mutations indicates that (i) the CoblI and CobIlI mutations are contiguous-that is, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…Several explanation have been proffered (11,17,48,49). In any model, the phosphoribosyltransferase reaction required for CobIII function must be performed by some other protein(s).…”
Section: Discussionmentioning
confidence: 99%
“…Several explanation have been proffered (11,17,48,49). In any model, the phosphoribosyltransferase reaction required for CobIII function must be performed by some other protein(s).…”
Section: Discussionmentioning
confidence: 99%
“…Strain JE50, which carries insertion cob-62::Mu dl1734(Kmr), served as donor in a transductional cross with JE1540 [cob-369 cob-236::TniOd(Tcr) cobA366:: Tnl0d(Cmr)] as recipient. The cob-369 mutation was 97% cotransducible with the cob-236: :Tnl0d(Tcr) marker, an insertion known to map in the downstream part of the CobI region of the cob operon (8).…”
Section: Methodsmentioning
confidence: 99%
“…All plasmids used in this study are listed in Table 1 and were derived from pJE2 (8). Plasmid pJO1 was generated by subcloning the approximately 3.4-kb S1 nuclease-blunted AatII fragment of pJE2 into the multiple cloning site of plasmid pSU21 (16), which had been previously digested with HincII.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic studies have shown that most of the B12 synthetic genes are located in the cob operon at minute 41 of the genetic map (13,20). The phenotypic defect of these mutants can be corrected by supplying exogenous cyanocobalamin (CN-B12).…”
mentioning
confidence: 99%